2016
DOI: 10.1007/s00227-016-2860-8
|View full text |Cite
|
Sign up to set email alerts
|

On the absence of genetic differentiation between morphotypes of the ballan wrasse Labrus bergylta (Labridae)

Abstract: The ballan wrasse, Labrus bergylta (Labridae), is a protogynous hermaphrodite fish common in the northeastern Atlantic from Norway to Morocco. It is a commercially important resource for local fisheries and is currently being used as cleaner fish to control sea lice in salmon 1,*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…Although this study did not control for morphotypes, and this is still an ongoing subject of research, results obtained in [32] using the same genetic markers point to the conclusion that our results are not affected by it.…”
Section: Discussionmentioning
confidence: 81%
“…Although this study did not control for morphotypes, and this is still an ongoing subject of research, results obtained in [32] using the same genetic markers point to the conclusion that our results are not affected by it.…”
Section: Discussionmentioning
confidence: 81%
“…In all cases, population trends by species obtained from different sources were normalized to the interview-derived scale (from −2 to 2). The two morphotypes of ballan wrasse Labrus bergylta (Ascanius, 1767; Almada et al, 2016;Quintela et al, 2016), pinto (spotted and reddish) and maragota (plain greenish or brown) (sensu Villegas-Ríos et al, 2013) were treated separately when possible.…”
Section: Comparison Between Interviews and Biological Datamentioning
confidence: 99%
“…Since it has been suggested that there are two morphotypes of L. bergylta (Almada et al , 2016; Quintela et al , 2016), that differ in their colour (i.e. ‘Pinto’, a spotted and reddish form, and ‘Maragota’, plain greenish or brown; Villegas-Ríos et al , 2013), they were treated separately in this paper.…”
Section: Methodsmentioning
confidence: 99%